Evaluating the strategic performance of agricultural projects by adopting international indicators - حافظ, عبد الناصر علك; صادق, اسعد عباس (Journal of Economics and Administrative Sciences, 2018)
The aim of this research is to test the relationship of influence and correlation between strategic performance and its five dimensions (financial dimension, after internal processes, after internal customer satisfaction, after learning and growth, environmental and social dimension), by adopting international indicators in agricultural projects To determine the extent of the differences between the research variable and its dimensions, and then try to come out with a number of recommendations that contribute to the evaluation of agricultural projects and their performance by diagnosing and treating deviations, and based on the importance of the research topic in agricultural institutions. Institutions of the Environment and Society The methodology (descriptive analysis) was adopted in completing this research. Data were collected from 78 respondents representing the research community, exclusively and comprehensively, namely (the general manager and his assistant, project managers, heads of departments, (43), using personal interviews as an aid in their collection, and the research on Excel2010, Amos.V18, SPSS (V23), with the methods of descriptive statistics (percentage, standard deviation, arithmetic mean, regression Simple linear, multiple linear regression, coefficient of selection) to force test His. The results of the research were a number of conclusions, including the start of new projects without the completion of old ones, and the same team, which leads to more situations (confusion and waste) of time and effort, noted neglect of analysis of the environment of external and internal projects, under the strengths and weaknesses of the projects, Weak supervision and control programs, weak regulations and project control standards, which may not be commensurate with the project conditions and actual reality, as well as the fact that these standards are general for all projects, without considering the specificity of each project.